Analyzing the Diverging Diamond Interchange Using Discrete Event Simulation. (21st November 2012) - Anderson, Michael; Schroer, Bernard; Moeller, Dietmar
Abstract : The diverging diamond interchange (DDI) can improve traffic flow by limiting the number of phases in the traffic signals and improve safety by eliminating left turns. A few instillations of these interchanges have been constructed and there is great potential to construct more. In an effort to develop a methodology to evaluate these interchanges, this paper presents the development of a discrete event simulation model of the diverging diamond interchange (DDI). Specific emphasis is on using simulation to model the DDI, a description of the operation of the simulation model, and using simulation to understand the operation of the DDI. The paper concludes that the use of the simulation package allows for rapid evaluation of the DDI and demonstrates that this interchange design will not work in all locations.